Legal Responsibility for Corruption Policies in Digital-Based Local Government Goods and Services Procurement Mechanisms - Ramadhani, Syifa Utari; Bawono, Bambang Tri (UNISSULA Semarang, 2025)
Policy corruption in digital-based local government procurement mechanisms is a serious threat to the integrity of governance and national development. This phenomenon specifically occurs when public regulations or policies, such as overly specific technical requirements or qualification criteria that deviate from fair procurement principles, are manipulated to benefit certain goods/services providers who have close ties with policy makers. This manipulation exploits gaps in digital systems that should be designed to increase transparency and accountability, for example by deliberately creating ambiguity in electronic auction specifications or limiting access to digital platforms for other potential providers. Therefore, the author raises the title